2021
DOI: 10.1038/s41598-021-94013-x
|View full text |Cite
|
Sign up to set email alerts
|

$$\mu PT$$ statistical ensemble: systems with fluctuating energy, particle number, and volume

Abstract: Within the theory of statistical ensemble, the so-called $$\mu PT$$ μ P T ensemble describes equilibrium systems that exchange energy, particles, and volume with the surrounding. General, model-independent features of volume and particle number statistics are derived. Non-analytic points of the partition function are discussed in connection with divergent fluctuations and ensemble equivalence. Qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…In this paper, we provide a general framework for calculating the uncertainty relation for each pair of thermodynamic intensive and extensive variables. Where we regarded the transition approach between different ensembles at the thermodynamic limit via a Legendre transformation [23][24][25][26]. We demonstrated that our results are consistent for all ensembles in any coupling regime.…”
Section: Canonical Ensemblesupporting
confidence: 60%
See 2 more Smart Citations
“…In this paper, we provide a general framework for calculating the uncertainty relation for each pair of thermodynamic intensive and extensive variables. Where we regarded the transition approach between different ensembles at the thermodynamic limit via a Legendre transformation [23][24][25][26]. We demonstrated that our results are consistent for all ensembles in any coupling regime.…”
Section: Canonical Ensemblesupporting
confidence: 60%
“…In addition, one can redefine S from ln Z by a Legendre's transformation [23][24][25][26]. Let us consider an infinitesimal change d A i and dλ i of A i and λ i in equilibrium, respectively.…”
Section: Equilibrium Entropymentioning
confidence: 99%
See 1 more Smart Citation